Genetic variation reveals the therapeutic potential of BRSK2 in idiopathic pulmonary fibrosis - Zhe Chen; Mingyang Tang; Nan Wang; Jiangjiang Liu; Xiaoyan Tan; Haitao Ma; Jing Luo; Kai Xie (BMC Medicine)
Abstract Background Current research underscores the need to better understand the pathogenic mechanisms and treatment strategies for idiopathic pulmonary fibrosis (IPF). This study aimed to identify key targets involved in the progression of IPF. Methods We employed Mendelian randomization (MR) with three genome-wide association studies and four quantitative trait loci datasets to identify key driver genes for IPF. Prioritized targets were evaluated for respiratory insufficiency and transplant-free survival. The therapeutic efficacy of the core gene was validated in cellular and animal models. Additionally, we conducted a comprehensive evaluation of therapeutic value, pathogenic mechanisms, and safety through phenome-wide association study (PheWAS), mediation analysis, transcriptomic analyses, shared causal variant exploration, DNA methylation MR, and protein interactions. Results Multiple MR results revealed that BRSK2 has a significant pathogenic impact on IPF at both transcriptional and translational levels, with a lung tissue-specific association (OR = 1.596; CI, 1.300–1.961; Pval = 8.290 × 10 − 6). BRSK2 was associated with IPF progression driven by high-risk factors, with mediation effects ranging from 34.452 to 69.665%. Elevated BRSK2 expression in peripheral blood mononuclear cells correlated with reduced pulmonary function, while increased circulating BRSK2 levels suggested respiratory failure and shorter transplant-free survival in IPF patients. BRSK2 silencing attenuated lung fibrosis progression in cellular and animal models. Transcriptomic integration identified PSMB1, CTSD, and CTSH as significant downstream effectors of BRSK2, with PSMB1 showing robust shared causal variant support (PPH4 = 0.800). Colocalization analysis and phenotype scan deepened the pathogenic association of BRSK2 with IPF, while methylation MR analysis highlighted the critical role of epigenetic regulation in BRSK2-driven IPF pathogenesis. PheWAS revealed no significant drug-related toxicities for BRSK2, and its therapeutic potential was further underscored by protein interaction analyses. Conclusions BRSK2 is identified as a critical pathogenic factor in IPF, with strong potential as a therapeutic target. Future studies should focus on its translational implications and the development of targeted therapies to improve patient outcomes.